Can the World Bank Build Social Capital? The Experience of Social Funds in Malawi and Zambia - Vajja, Anju; White, Howard (2012)
Social funds have been one of the main manifestations of the World Bank's move toward promoting projects with a participatory orientation. Supporters of social funds argue that participation in social fund activities builds community social capital. Critics of the Bank's use of social capital argue that it ignores power structures but these critics have focused on the Bank's research rather than its operations. This paper examines 'social capital' in a project context: social funds in Malawi and Zambia. In contrast to the model of collective action suggested by proponents of social funds, it is shown that the nature of community participation is indeed shaped by existing power and social relations. Project identification and execution is led by a small number of people in the community, usually the head teacher in cooperation with the PTA and traditional authorities. The community is then mobilised using the traditional structures of village headmen. Most community members participate actively in making bricks, but passively in decision making. However, this process should be seen as an institutional adaptation to what social funds offer, not elite capture. Most community members are satisfied with the outcome, although the chosen project is not what they would have chosen themselves. Given these processes, social funds do little to build social capital but instead, appear to be users of existing social capital.